Implementation and development of K. F. Sedov's scientifi c ideas in the content of the technology of professional training of speech therapists - Bochkareva, Tatiana A.; Koshcheeva, Olga V. (Saratov State University, 2024)
The relevance of the research is due to the necessity to generalize the scientifi c research of K. F. Sedov in the context of formation of ontolinguistic, psycholinguistic and other areas of development of the Department of Speech Therapy and Psycholinguistics of Saratov State University, as well as in the aspect of implementing the research in the content of the technology of speech therapists’ professional training. Purpose: to summarize the scientifi c and methodological heritage of K. F. Sedov and the experience of its practical application in training the students majoring in ‘Speech Therapy’ qualifi cation at Saratov State University and in the research of teachers of the Department of Speech Therapy and Psycholinguistics. Methods (tools): comparative analysis of the data from scientifi c and bibliographic sources such as dissertations, monographs, articles, programs and educational materials of the Department of Speech Therapy and Psycholinguistics. Results. For the fi rst time, the analysis of the scientifi c heritage of K. F. Sedov was carried out from the point of view of its implementation and development in the content of the technology of professional training of speech therapists at the Department of Speech Therapy and Psycholinguistics, particularly, in the courses taught by the Department, in the works of teachers, and in the topics of graduation papers. The study has revealed the continuity of the conceptual approaches of Prof. K. F. Sedov in the methodological and practical activities of the Department, in the content of the technology of professional training of bachelors and masters majoring in Speech therapy. The study also presents the development of K. F. Sedov’s ideas in the scientifi c activities of teachers and students of the Department of Speech Therapy and Psycholinguistics in psycholinguistic, ontogenetic, speech genre and pragmasemiotic directions. The prospects for the development of scientifi c directions of the Department of Speech Therapy and Psycholinguistics in this perspective are outlined. They include further study of the peculiarities of speech and thinking activity of children with severe speech disorders (TNR), of the psycholinguistic foundations of speech therapy, of the peculiar use of psycholinguistic experiment in teaching speech therapy disciplines, as well as of the active inclusion of a speech genre approach in developing the professional competencies of speech therapists. Practical significance. The practical signifi cance of the research lies in the possibility of using the results of analytics in the development of the content of the technology of professional training of speech therapists in other universities.